THE EFFECT OF GARLIC (Allium sativum) EXTRACT BY DRINKING WATER TO EGG PRODUCTION OF LOHMANN BROWN LAYING HENS AGE OF 22-30 WEEKS - N., Hasanah; Bidura, I G. N. G.; Puspani, E. (Jurnal Peternakan Tropika; Vol 6 No 2 (2018): May - August 2018, 2018)
This research aims to know the effect of giving the garlic extract ( Alli u m sativum ) through drinking water toward the production of chicken egg Lohmann Brown aged 22-30 weeks. This research was conducted in Dajan Peken Village, Tabanan-Bali District for 3 months, using 36 Lohmann Brown chicks aged 22 weeks. The design of this research was Completely Randomized Design (CRD) with 3 treatments and 6 replications. The three treatments were chickens given drinking water without the use of garlic extract (B0), chickens were given drinking water with the addition of 3% garlic extract (B1), and chickens were given drinking water with the addition of garlic extract 6% (B2). The feed is given 2 times a day and drinking water is given in ad libitum . The variables observed in this research were ration consumption, drinking water consumption, total egg weight, egg weight, egg and FCR (Feed Convertion Ratio). The results showed that giving garlic water extract of garlic into drinking water at level 3% and 6% significantly able (P<0,05) to increased feed ration consumption, drinking water consumption, total egg weight, egg weight and egg count and reduced FCR significantly (P>0.05) on Lohmann Brown chicken the age of 22-30 weeks. From the results of this research, it can be concluded that giving garlic extract ( Alli u m sativum ) at 3% and 6% level through drinking water can increase consumption of ration, drinking water consumption, total egg weight, egg number, egg weight, but lower FCR of chicken Lohmann Brown aged 22-30 weeks. Keywords: Garlic (Allium sativum), egg production, Lohmann Brown